Effect of ripeners on the nutrient concentrations of sugarcane leaves - Silva, Marcelo de Almeida [UNESP]; Santos, Hariane Luiz [UNESP]; Germino, Gabriel Henrique [UNESP]; Véliz, José Gerardo Espinoza (Taylor & Francis, 2023)
Using chemical ripeners in the sugarcane favors the increase of sucrose productivity, regulates the effects of adverse weather conditions for ripening, and promotes the anticipation of harvest. However, it can also modify the nutrient absorption, translocation, and accumulation process and, consequently, affect the nutrient cycling of the straw maintained on the soil surface. Thus, this research aimed to evaluate ripeners’ effects (glyphosate − 0.5 L ha−1; sulfometuron-methyl − 0.02 kg ha−1, and trinexapac-ethyl − 0.8 L ha−1) on the nutritional status of the sugarcane leaf canopy. Natural ripening maintained the highest levels of P and Zn throughout the time. The highest levels of N, P, and K were provided by trinexapac-ethyl in most of the evaluated periods, as well as contributing to the highest levels of Ca, Mg, and S, along with sulfometuron methyl, from 30 to 60 days after application (DAA). The highest levels of B and Zn were observed under sulfometuron methyl. On the other hand, glyphosate was the ripener responsible for the lowest nutrient concentrations in the leaf canopy, including N, Ca, Mg, and S at 45 DAA and B and Mn at 30 and 45 DAA. Considering the importance of maintaining the straw for nutrient cycling, in addition to being a ripener, trinexapac-ethyl contributed to the maintenance of high levels of nutrients in the leaf canopy in relation to the other ripeners, which suggests a greater possibility of availability of these nutrients for the ratoon development in the upcoming cycles.
Keywords: Macronutrients; micronutrients; nutritional status; plant growth regulators; Saccharumspp